Considerações acerca da objeção de consciência sob o prisma noético da logoteoria de Viktor Frankl. - Fonseca, Ramon Silva Silveira da (2020)
The present doctoral work aims to identify the performance of the values of logotheory in legal documents that deal with the practice of conscientious objection. As part of the investigation, specific objectives are proposed to present the conceptual aspects related to the conscientious objection, considering its historical and political context; to talk about the concepts of conscience in the philosophical and psychological spheres; to talk about the theory of values in the thought of the philosopher Max Scheler, as well as about its relation with the Franklian thought; finally, to compensate the logotheoric thinking highlighting the concept of conscience as an organ of meaning and thinking about values in franklian anthropology. It is considered as a hypothesis that the exercise of conscientious objection is a strategy for the preservation of aspects of the human being's noetic identity. Thus, the research was guided by the problem: how do the values of realization of the meaning of life express themselves in the practice of conscientious objection? Methodologically, the research is characterized as a qualitative, descriptive, basic study. The data were systematized using the software IRAMUTEQ making a lexical analysis of the content of the responses. Fifteen documents from the higher courts were selected. The results identified 4 classes in the dendrogram: (1) Procedural components, (2) Panoramic view; (3) Focal vision; and (4) Axiological elements. In the similitude analysis, a correlation was found between the words no and appeal, indicating the prevalence of refusal by the courts to accept the demands of conscientious objection. Another nucleus related the words teaching-education with society, person and pluralism, demonstrating how the demands of conscientious objection relate between individual and community values, highlighting the binomial teaching-education, due to the dimension of the data related to this theme. Furthermore, when the data was systematized by means of content analysis, it was identified that 53% (8) of the documents refer to the conscientious objection to mandatory military service, revealing this theme the most present in the judicial demands, especially in the of the Superior Court of Justice. 26% (4) refer to the demands of religious objection regarding the obligation to observe the precept day. Only 13% (2) of appeals were successful in guaranteeing the right to conscientious objection. The results obtained discussed from the perspective of Viktor Frankl's theory of values highlight the situationality and the uniqueness of values, as well as their hierarchical organization in which the judgment of demands is expressed and in the contemporization of different wills. Ademias, the relevance of the concept of illusion of meaning and falsification of values was perceived for the consideration of tolerance and respect for diversity.